VARIASI SPASIAL GETARAN TANAH AKIBAT GEMPABUMI (STUDI KASUS: RANGKAIAN GEMPABUMI SUMATERA UTARA 9-13 FEBRUARI 2017) - Sesar Prabu Dwi Sriyanto; Indah Fajerianti; Amalia Nasrurroh; Nur B Febryana; Indri Ifantyana; Kevin D Wicaksono; Market Sofyan (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
The ground motion that caused bythe earthquakee is dangerous since it can break down buildingsÂ. It is the result of convolution of source function and raypath function of seismic wave, including local site function on seismometer location. The aim of this study is to analyze the characteristic variations of spatial ground motion from 7 earthquake events happened from 9 till 13 on February 2017 in North Sumatra. Based on the recording of ground motion from 8 seismic stations around the epicenter, the value of the PGA (Peak Ground Acceleration) and PGV (Peak Ground Velocity) can be calculated. The analysis of local site and its influence to ground motion is also calculated using HVSR (Horizontal to Vertical Spectral Ratio) method. Generally, the value of the PGA and PGV are inversely equal to epicenter distance. The soft soil condition in seismic stations cause wave amplification resulted in the magnification of PGA and PGV value. Besides, the rupture directivity can also affect the value of peak ground motion. In this case, the value of the PGA and PGV tend to be high in the north area of the epicenter. It indicates that north area has the highest potential for seismic hazard than the south area if it is reviewed on this source.Keywords: spatial variation, peak ground motion, local site effect, rupture directivity